Rights-based freshwater governance for the twenty-first century: beyond an exclusionary focus on domestic water uses - van Koppen, Barbara; Hellum, A.; Mehta, L.; Derman, B.; Schreiner, B. (2016)
The UN recognition of a human right to water for drinking, personal and other domestic uses and sanitation in 2010 was a political breakthrough in states’ commitments to adopt a human rights framework in carrying out part of their mandate. This chapter explores other domains of freshwater governance in which human rights frameworks provide a robust and widely accepted set of normative values to such governance. The basis is General Comment No. 15 of the Committee on Economic, Social and Cultural Rights in 2002, which states that water is needed to realise a range of indivisible human rights to non-starvation, food, health, work and an adequate standard of living and also procedural rights to participation and information in water interventions. On that basis, the chapter explores concrete implications of the Comment for states’ broader infrastructure-based water services implied in the recognised need to access to infrastructure, rights to non-discrimination in public service delivery and respect of people’s own prioritisation. This implies a right to water for livelihoods with core minimum service levels for water to homesteads that meet both domestic and small-scale productive uses, so at least 50–100 l per capita per day. Turning to the state’s mandates and authority in allocating water resources, the chapter identifi es three forms of unfair treatment of smallscale users in current licence systems. As illustrated by the case of South Africa, the legal tool of “Priority General Authorisations” is proposed. This prioritises water allocation to small-scale water users while targeting and enforcing regulatory licences to the few high-impact users.